Difference between revisions of "009A Sample Midterm 2, Problem 5"

From Math Wiki
Jump to navigation Jump to search
 
(2 intermediate revisions by the same user not shown)
Line 6: Line 6:
  
 
<span class="exam">(c) &nbsp; <math style="vertical-align: -18px">h(x)=\frac{(5x^2+7x)^3}{\ln(x^2+1)} </math>
 
<span class="exam">(c) &nbsp; <math style="vertical-align: -18px">h(x)=\frac{(5x^2+7x)^3}{\ln(x^2+1)} </math>
 +
<hr>
 +
[[009A Sample Midterm 2, Problem 5 Solution|'''<u>Solution</u>''']]
  
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
+
[[009A Sample Midterm 2, Problem 5 Detailed Solution|'''<u>Detailed Solution</u>''']]
!Foundations: &nbsp;
 
|-
 
|'''1.''' '''Chain Rule'''
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{d}{dx}(f(g(x)))=f'(g(x))g'(x)</math>
 
|-
 
|'''2.''' '''Trig Derivatives'''
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{d}{dx}(\sin x)=\cos x,\quad\frac{d}{dx}(\cos x)=-\sin x</math>
 
|-
 
|'''3.''' '''Quotient Rule'''
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{d}{dx}\bigg(\frac{f(x)}{g(x)}\bigg)=\frac{g(x)f'(x)-f(x)g'(x)}{(g(x))^2}</math>
 
|-
 
|'''4.''' '''Derivative of natural logarithm
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{d}{dx}(\ln x)=\frac{1}{x}</math>
 
|}
 
  
  
'''Solution:'''
 
 
'''(a)'''
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|First, we use the Chain Rule to get
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>f'(x)=3\tan^2(7x^2+5)(\tan(7x^2+5))'.</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|Now, we use the Chain Rule again to get
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{f'(x)} & = & \displaystyle{3\tan^2(7x^2+5)(\tan(7x^2+5))'}\\
 
&&\\
 
& = & \displaystyle{3\tan^2(7x^2+5)\sec^2(7x^2+5)(7x^2+5)'}\\
 
&&\\
 
& = & \displaystyle{3\tan^2(7x^2+5)\sec^2(7x^2+5)(14x).}
 
\end{array}</math>
 
|}
 
 
'''(b)'''
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|First, we use the Chain Rule to get
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>g'(x)=\cos(\cos(e^x))(\cos(e^x))'.</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|Now, we use the Chain Rule again to get
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{g'(x)} & = & \displaystyle{\cos(\cos(e^x))(\cos(e^x))'}\\
 
&&\\
 
& = & \displaystyle{\cos(\cos(e^x))(-\sin(e^x))(e^x)'}\\
 
&&\\
 
& = & \displaystyle{\cos(\cos(e^x))(-\sin(e^x))(e^x).}
 
\end{array}</math>
 
|}
 
 
'''(c)'''
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|First, we use the Quotient Rule to get
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>h'(x)=\frac{\ln(x^2+1)((5x^2+7x)^2)'-(5x^2+7x)^2(\ln(x^2+1))'}{(\ln(x^2+1))^2}.</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|Now, we use the Chain Rule to get
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{h'(x)} & = & \displaystyle{\frac{\ln(x^2+1)((5x^2+7x)^2)'-(5x^2+7x)^2(\ln(x^2+1))'}{(\ln(x^2+1))^2}}\\
 
&&\\
 
& = & \displaystyle{\frac{\ln(x^2+1)2(5x^2+7x)(5x^2+7x)'-(5x^2+7x)^2\frac{1}{x^2+1}(x^2+1)'}{(\ln(x^2+1))^2}}\\
 
&&\\
 
& = & \displaystyle{\frac{\ln(x^2+1)2(5x^2+7x)(10x+7)-(5x^2+7x)^2\frac{1}{x^2+1}(2x)}{(\ln(x^2+1))^2}.}
 
\end{array}</math>
 
|}
 
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;
 
|-
 
|&nbsp; &nbsp; '''(a)''' &nbsp; &nbsp; <math>f'(x)=3\tan^2(7x^2+5)\sec^2(7x^2+5)(14x)</math>
 
|-
 
|&nbsp; &nbsp; '''(b)''' &nbsp; &nbsp; <math>g'(x)=\cos(\cos(e^x))(-\sin(e^x))(e^x)</math>
 
|-
 
|&nbsp; &nbsp; '''(c)''' &nbsp; &nbsp; <math>h'(x)=\frac{\ln(x^2+1)2(5x^2+7x)(10x+7)-(5x^2+7x)^2\frac{1}{x^2+1}(2x)}{(\ln(x^2+1))^2}</math>
 
|}
 
 
[[009A_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]
 
[[009A_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 14:22, 9 November 2017

Find the derivatives of the following functions. Do not simplify.

(a)  

(b)  

(c)  


Solution


Detailed Solution


Return to Sample Exam